La justicia administrativa en España - Meilán Gil, José Luis (Revista de Derecho, 2019)
The present work contains an analysis of the contentious-administrative Jurisdictionin Spain, taking as starting point the profound revision produced in the judicialsystem by the approval of the 1978 Spanish Constitution. Some of the most significantaspects of the current regulation, contained in Law 29/1998, dated July 13th aretaken into account.
Keywords: Justice; Public Administration; Administrative Law